Prevalence and impact of comorbid alcohol use disorder in bipolar disorder: A prospective follow-up study. (April 2016) - Simhandl, Christian; Radua, Joaquim; König, Barbara; Amann, Benedikt L
Objective: Alcohol use disorder may very well increase the likelihood of affective episodes in bipolar disorder, but prospective data on survival are inconsistent. Method: The authors examined the prevalence of alcohol use disorders and their impact on the risk of relapse. A total of 284 consecutively admitted International Classification of Diseases-10 bipolar I ( n  = 161) and II ( n  = 123) patients were followed up naturalistically over a period of 4 years. Results: The prevalence of alcohol use disorders was higher in bipolar II disorder than in bipolar I disorder (26.8% vs 14.9%; χ 2  = 5.46, p  = 0.019), with a global prevalence of alcohol use disorders of 20.1% in the whole sample. A total of 8.7% of bipolar I patients suffered from alcohol abuse and 6.2% from alcohol dependency, whereas 13% bipolar II patients had alcohol abuse and 13.8% alcohol dependency. Male bipolar subjects had a higher prevalence of alcohol use disorders than female patients (38.3% vs 12.8%; χ 2  = 21.84, p -value < 0.001). The presence of alcohol use disorders was associated with an increased risk of depressive relapse in bipolar I patients (Cox regression analysis hazard ratio = 2.7, p  = 0.005). The increased risk was not modulated by medication. Conclusion: Our data underline the negative long-term impact of alcohol use disorders on bipolar disorder with more depressive bipolar I episodes and the importance of its detection and treatment.